The four-step process for redesigning work - Gratton, Lynda (MIT Sloan Management Review, 2022)
Fear of failure weighs heavily on many leaders tasked with managing new workplace expectations. Tackling uncertainties begins by seeing these challenges not simply as binary judgments (office or home; full time or part time) but as the impetus to give work a structural overhaul. Leaders are redesigning work by moving through four steps: understanding people, networks, and jobs; reimagining how work gets done; modeling and testing redesign ideas against core principles; and taking action widely.
"Reprint 64129."
Keywords: Personnel management; Organizational change; Management by exception; Telecommuting; Virtual work teams; Flextime; Personnel; Direction; Changement organisationnel; Gestion par exceptions; Équipes virtuelles; Horaires variables de travail